Peripheral cytokine levels as novel predictors of survival in cancer patients treated with immune checkpoint inhibitors: A systematic review and meta-analysis - Mao, Xin-Cheng; Yang, Chun-Cheng; Yang, Ya-Fei; Yan, Lun-Jie; Ding, Zi-Niu; Liu, Hui; Yan, Yu-Chuan; Dong, Zhao-Ru; Wang, Dong-Xu; Li, Tao (Frontiers in Immunology, 2022)
Background Early identification of patients who will benefit from immune checkpoint inhibitors (ICIs) has recently become a hot issue in cancer immunotherapy. Peripheral cytokines are key regulators in the immune system that can induce the expression of immune checkpoint molecules; however, the association between peripheral cytokines and the efficiency of ICIs remains unclear. Methods A systematic review was conducted in several public databases from inception through 3 February 2022 to identify studies investigating the association between peripheral cytokines (i.e., IL-1β, IL-2, IL-2RA, IL-2R, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IL-15, IL-17, TNF-α, IFN-γ, and TGF-β) and ICI treatment. Survival data, including overall survival (OS) and/or progression-free survival (PFS), were extracted, and meta-analyses were performed. Results Twenty-four studies were included in this analysis. The pooled results demonstrated that the pretreatment peripheral levels of IL-6 (univariate analysis: HR = 2.53, 95% CI = 2.21–2.89, p < 0.00001; multivariate analysis: HR = 2.21, 95% CI = 1.67–2.93, p < 0.00001) and IL-8 (univariate analysis: HR = 2.17, 95% CI = 1.98–2.38, p < 0.00001; multivariate analysis: HR = 1.88, 95% CI= 1.70–2.07, p < 0.00001) were significantly associated with worse OS of cancer patients receiving ICI treatment in both univariate and multivariate analysis. However, high heterogeneity was found for IL-6, which might be attributed to region, cancer type, treatment method, sample source, and detection method. Conclusion The peripheral level of IL-8 may be used as a prognostic marker to identify patients with inferior response to ICIs. More high-quality prospective studies are warranted to assess the predictive value of peripheral cytokines for ICI treatment.